Binary Mn-FeOx nanoflakes supported on CNT by an one-step redox method for low temperature NO reduction with NH3. (19th May 2021) - Zhang, Yanbing; Chen, Yingzan; Huang, Jinhe; Song, Chengjian; Cheng, Xianglong; Ren, Haibo; Wang, Xie
Abstract: Binary Mn-FeOx /CNT-OSR catalysts were prepared by an one-step redox method, and showed 44%–83.7% NO conversion at 80 °C–180 °C. The catalytic activity of the 0.06 Mn-FeOx /CNT-OSR catalyst is optimum and reaches 65.9%–83.7% at 80 °C–180 °C, resulting from the generation of high valence of MnO2 and Fe2 O3 with weak crystallinity.